MORPHOGENETIC AND IN VITRO STUDIES OF THE SHOOT APICES OF PHARBITIS CHOIS, STRAIN VIOLET IN RELATION TO PHOTOPERIODIC INDUCTION - BHAR B., DILBAGH S. (My University, 2015)
In this investigation the methods of obtaining uniform and maximum germination of seeds and of producing contamination-free cultures of the shoot apices of Pharbitis nil have been examined and established.
Flowering response of vegetative seedlings of different ages has been investigated as related to photoperiodic induction. The sequence of orphological changes at the shoot apex has been examined in Pharbitis nil, in relation to an inductive photoperiod. The phenomenon of revrersion has been investig~ted, by excising and culturing in vitro the shoot apices from intact plants, at varying periods following inductive period. Floral induction in cultured vegetative apices has been attempted.
It is shown that the intact plants respond differently in flower formation to an inductive photoperiod. The apices vary in morphological configuration and cytologic zonation, during the germination, vegetative and reproductive stages. The in vitro studies have also shown that the flowering process once initiated, cannot be reversed until and unless a mechanism inhibits its regulatory process in the early stages of transition. The leaf is the primary site of photoinduction. Floral induction is related to the presence of a minimum leaf area.
pharbitis, vitro, intact, plants